Antiviral treatment in outpatients with herps zoster in six major areas of China, 2010–2019 - Yu, Zhenwei; Zhao, Yuhua; Jin, Jiayi; Zhu, Jianping; Yu, Lingyan; Han, Gang (Frontiers in Public Health, 2022)
Objective The objective of this study was to assess the status and trends of antiviral treatment in outpatients with herpes zoster in China. Methods Prescription data on antiviral drugs were extracted from the database of the Hospital Prescription Analysis Program of China according to the inclusion criteria. Yearly prescriptions and costs were calculated, and trends were analyzed. The distribution of defined daily costs (DDCs) of valaciclovir and famciclovir were analyzed, and trends in the median DDCs were identified. Results A total of 132911 prescriptions from 49 hospitals located in six major areas of China were included in the analysis. The yearly prescriptions containing antivirals increased from 8819 in 2010 to 16361 in 2019. The percentage of prescriptions for patients aged 65 years and above also increased (27.7% in 2010 to 31.0% in 2019), and the number of prescriptions for females was higher than those for males (P<0.001). The average cost of antivirals per prescription decreased; thus, the yearly cost showed no increasing trend. The main prescribed antivirals were valaciclovir and famciclovir, which progressively increased in prescriptions. The use of acyclovir decreased during the study period. Prescriptions containing topical formulations, acyclovir and penciclovir, both increased. The DDCs of valaciclovir and famciclovir decreased dramatically. Conclusion The use of antivirals has increased over the decade, while the cost has not. Antiviral treatments adhere well to recent recommendations, except for the use of topical antivirals. The findings of this study may benefit the healthcare source allocation and management of herpes zoster in China.